High-level biathletes with a fast-start pacing pattern improve time-trial skiing, without changes in shooting performance, by using a more even pacing strategy - Losnegard, T.; Lund-Hansen, M.; Stubbe, E. V.; Granrud, E. D.; Luchsinger, H.; Sandbakk, Ø.; Kocbach, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: An athlete`s distribution of energetic resources, described as their "pacing strategy," have a substantial influence on performance in various endurance sports (Abbiss & Laursen 2008). We investigated whether reducing the start pace in biathlon athletes with the most pronounced fast-start pacing pattern influence rollerski performance, hits and precisions of prone and standing shooting and rate of perceived exertion (RPE).